Effect of Petroleum Fuels and Lubricants on Soil Properties of Auto-mechanic Workshops and Garages in Cape Coast Metropolis, Ghana - H.D. Nyarko; G.C. Okpokwasili; O.F. Joel; I.A.K. Galyuon (Journal of Applied Sciences and Environmental Management, 2019)
Soil properties of petroleum hydrocarbon contaminated soils from automobile mechanical shops in the Cape Coast Municipality of the Central Region of Ghana were investigated to assess their alternation due to the petroleum hydrocarbon contamination. Soil samples were collected from eight automobile mechanical shops and control sites and analyzed using standard protocols. The mean particle size distribution followed the order: sand 64.79±19.47 > silt 22.81±9.47 > 12.40±14.68. The distributions for the control samples followed a similar order. The particle size distribution of soils from the study sites was not significantly different from those of the control sites (p<0.05). There were greater variations in soil characteristics of control samples than those of the contaminated soils, with significant differences observed between most of the soil characteristics of the two sites (p<0.05). Significant correlations were observed between some soil properties, between temperature and conductivity (p< 0.01; r=-0.689); temperature and organic matter (p< 0.05; r= 0.422); pH and conductivity (p< 0.01; r= 0.549); pH and nitrate (p< 0.05; r= 0. 430); pH and Phosphate (p< 0.01; r= 0.652); nitrate and phosphate (r= 0. 728, p< 0.01), organic matter and phosphate (p< 0.01; r= 0. 692); moisture and nitrate (r= 0. 787, p< 0.0); and between moisture and phosphate (r= 0. .633, p< 0.01). Petroleum hydrocarbon contamination altered soil properties and may adversely affect sensitive bacteria.